A New Approach to Estimate the Potential Assets Loss due to Dam-Break Event in Indonesia - Farrell Wiguna; Doddi Yudianto; Bobby Minola Ginting; Albert Wicaksono (Journal of Infrastructure & Facility Asset Management, 2022)
A dam break is a devastating natural catastrophe that can lead to huge losses. In general, the severity of a disaster can be determined by the amount of damage it causes. The greater the loss, the more severe the disaster and vice versa. However, determining the potential asset loss as a result of a disaster is a challenging task. So far, there is no method for calculating potential asset loss that is specifically made for dam-break disasters. Therefore, this study proposes a new approach in calculating the potential asset loss for a dam-break. In this study, the potential asset loss is calculated by considering four factors, namely the Potential Loss of Lives (PLOL), Potential Loss of Incomes (PLOI), Potential Loss of Houses Damage (PLOHD), and Potential Loss of Productive Land (PLOPL). In addition, the study calculates the potential asset loss of the Ketro Dam dam-break disaster. Based on the evaluation results, the PLOL might reach Rp. 26,419,715,661.  PLOI might reach maximum value of  Rp. 1,185,600,000. PLOHD might reach maximum value of Rp. 4,255,325,000. And  lastly , PLOPL might reach maximum value of  Rp. 25,375,080,780. Thus, the potential asset loss for the Ketro Dam dam-break disaster based on the analysis can reach Rp. 57,235,721,441 or USD 4,026,304.